A Case Report of Preeclampsia Causing Severe Hyponatremia: Rare or Rarely Reported?. Issue 8 (15th April 2019) - Grimmett, Wallace; Lee, Julie; Doherty, James; Cheung, Benjamin; Chinthamuneedi, Meher
Abstract : Preeclampsia presenting as severe hyponatremia is an enigma of modern obstetric practice. The hyponatremia can cause severe maternal neurological morbidity, including cerebral edema and seizures. Neonates, with serum sodium reflecting maternal levels, are also at risk. Despite this, the literature remains ambiguous about its incidence, the pathophysiology is poorly understood, and guidelines on preeclampsia (including those of the American College of Obstetricians and Gynecologists) do not discuss the issue. This case of preeclampsia associated with severe hyponatremia in a laboring woman highlights these issues.